The role of strategic approaches in developing new products on the process of sports finance A case study of the National Telecommunication Corporation of Algeria - Ooredoo - (formerly star) in sports finance - Taibi , ahmed (sports creativity, 2025)
The new organizations work to protect and develop it's market share within plenty ways, one of them is adopting the ANSOFF that takes in consideration the the new product development. So the diversification is the last case of the matrix that contains the working of the organization out of activity, so being inside the sport's field and finance the athletes and clubs ...etc, Is one tool that helps organizations to keep working and fighting in markets by advertising it's products